If I Am Her - Hollensteiner, Shadi (Satura, 2026)
If I Am Her grapples with body dysmorphia and the struggle to reconcile contemporary standards of beauty with the mythic ideal embodied by Aphrodite. The poem embodies the speaker’s fractured relationship with their own reflection, confronting internalized shame and the pressure to disappear into culturally sanctioned silhouettes. Through metaphors and imagery the poem invokes the goddess not as a marble icon, but as a living, sensuous archetype whose form challenges narrow norms. Yet the knowledge of this divine lineage remains painfully distant. Between reverence and vulnerability, the speaker questions why belief in beauty remains foreign, even when its existence is carved in their very skin.